A comparison of the wood anatomy of 11 species from two cerrado habitats (cerrado s.s. and adjacent gallery forest) - Sonsin, Julia O. [UNESP]; Gasson, Peter E.; Barros, Claudia F.; Marcati, Carmen Regina [UNESP] (Wiley-Blackwell, 2012)
A comparative study of the secondary xylem (wood) anatomy of 11 species (38 specimens) occurring in cerrado s.s. and the adjacent gallery forest (both cerrado s.l. habitat) was made with the aim of identifying the anatomical characteristics of ecological value and correlating them with the environmental conditions. The anatomical features that vary, in general, between the two habitats are: growth ring distinctness (well or poorly defined); tyloses and deposits (more abundant in cerrado specimens); gelatinous fibres (more evident in cerrado specimens and in different patterns between habitats); variation in paratracheal and banded parenchyma (more abundant in cerrado); and more cells per parenchyma strand in cerrado. In general, gallery forest specimens have wider vessels, fewer vessels per square millimetre and larger intervessel pits, indicating more efficient water conduction, whereas cerrado s.s. specimens are the opposite, with low vulnerability and mesomorphy indices, demonstrating greater safety under conditions of water stress. (c) 2012 The Linnean Society of London, Botanical Journal of the Linnean Society, 2012, , .
Keywords: comparative wood anatomy; ecological wood anatomy; safety versus efficiency